Situated Design-Thinking in Architectural Practice: - Laura Malinin (Ardeth, 2018)
Nearly thirty-five years ago Donald Schön proposed an epistemology of design practice as an antidote to the crisis of legitimacy in architecture and other professional design disciplines. His theory of reflective practice is popular in teacher and nursing education programs and ‘design-thinking’ has gained credibility to promote innovation in business. Yet he failed to provide the epistemic credibility for architectural practice he promised. This critical analysis compares constructs in Schön’s theory against knowledge from mind and brain science to assess their validity and limitations. Findings inform suggestions for extending his theory toward developing a more complete epistemology of architectural practice.